Biological effects and toxicity mechanisms of polystyrene nanoplastics: A review - Wenxia BU; Xinyuan ZHAO; Xiaoke WANG; Juan TANG (环境与职业医学, 2023)
Polystyrene nanoplastics (PS-NPs) are widely used in industry, pharmaceutical and consumer packaging materials, and medical products. The biological health impacts of PS-NPs are receiving increasing attention. Therefore, it is necessary to conduct a literature review of in vitro and in vivo experimental studies from a biological mechanism perspective. Based on the latest research results at home and abroad, this review introduced the characteristics and cell internalization of PS-NPs in cytotoxicity experiments, and summarized the effects of PS-NPs on cytotoxic targets such as mitochondria, lysosomes, proteins, and DNA. In addition, the influencing factors of the health effects of PS-NPs were analyzed from the aspects of physical and chemical properties and cell types. Finally, by discussing the current research hotspots of cytotoxicity mechanism and biological effects, it was anticipated to provide a reference for the health risk management and biological safety assessment of PS-NPs.